Victim behaviour as a functional adaptation - Muzychenko, Diana S. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
The various manifestations of victimisation experience are under discussion in the article. Proposed systematisation, theoretical and empirical grounds of distinction of victimisation. The existing types of victimisation are compared in terms of predictors and impact on personality traits. The indicators of potentially detectable propensity to victim behaviour are related with the factual data of victimisation. According to the results of the study, a correlation was found between the features of adaptation undertaken in a victimisation situation and a high level of propensity for a certain type of victim behaviour at the current time. The patterns learned in the interpersonal interaction and socialisation are associated with the attitudes of readiness for the active self-harm creation or allowing a threat. Increased vulnerability comes from the forming model of regulation of relationships with the environment. The change in the hierarchy of priorities in the sphere of motivation and needs is considered as a mediating link. Established personality traits integrate the adaptation experience, being functional in a circumstances of victimisation.
Keywords: victim behaviour; personality factors; victimisation experience; situational factors; adaptation